Results of salmon fishery in the North Pacific Ocean and adjacent waters of the Arctic Ocean in 2024 - S. L. Marchenko (Известия ТИНРО, 2025)
Results of salmon fishery in 2024 are briefly presented for the Far East of Russia, Arctic, Japan, and northwestern North America.